2020
DOI: 10.1208/s12249-019-1609-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Efficacy of Silymarin Liquisolid in Isoproterenol Prompted Myocardial Infarction in Rats

Abstract: Myocardial infarction (MI) is the principal cause of death in many countries. Silymarin (SM) is a herbal antioxidant and can be efficiently used in preventing cardiovascular diseases (CVDs). The study is aimed to enhance the absorption rate and biological activity of SM by using liquisolids besides investigating the cardioprotective activity of SM and its selected liquisolid formula against isoproterenol prompted cardiotoxicity in rats. Eight formulae were prepared according to (2 3 ) full-factorial design. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Silibinin is a polyphenolic flavonoid extracted from the seeds of milk thistle ( Verdura et al, 2018 ), possessing strong antioxidant and cardioprotective activities ( Sheta et al, 2020 ). It has been successfully employed as a protective agent against arsenic-induced in vivo model of hepatotoxicity ( Muthumani and Prabu, 2012 ).…”
Section: Protective Effects Of Natural Products Against Environmental Toxins-induced Cardiotoxicitymentioning
confidence: 99%
“…Silibinin is a polyphenolic flavonoid extracted from the seeds of milk thistle ( Verdura et al, 2018 ), possessing strong antioxidant and cardioprotective activities ( Sheta et al, 2020 ). It has been successfully employed as a protective agent against arsenic-induced in vivo model of hepatotoxicity ( Muthumani and Prabu, 2012 ).…”
Section: Protective Effects Of Natural Products Against Environmental Toxins-induced Cardiotoxicitymentioning
confidence: 99%
“…The oleogel preparation was left aside for 48 h at room temperature to accomplish equilibrium, at this point the crystals begin to be formed through the oil (30). Half gram of each system was packed into the hard gelatin capsule (32) size 00 (33)(34)(35). No leakage was detected from all capsules packed with the various prepared Celecoxib formulae.…”
Section: Preparation Of Celecoxib Oleogel Formulaementioning
confidence: 99%
“…However, this technology has gained increased research interest more recently, and during the last decade enhanced dissolution from LS systems has been reported for various poorly soluble drugs (3)(4)(5)(6)(7)(8). Furthermore, recently reported in vivo studies showed improved bioavailability in the case of LS systems with different poorly soluble drugs (9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…For the industrial application of LS technology in tablet production it is of outmost importance to identify the factors affecting both flowability and compaction properties. The influence of different formulation variables, including the carrier and coating material type, the amount and type of liquid phase, the amount and type of viscosity increasing agent, and carrier to coating ratio, on flow properties and flowable liquid load of LS systems has been intensively investigated over the past years (9,10,(18)(19)(20)(21). For the application of this technology in tablet production not only good flowability, but also acceptable compaction properties have to be ensured.…”
Section: Introductionmentioning
confidence: 99%